(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
Eating disorders (ED) is an area of growing interest for health professionals. However, there are few Brazilian studies on the treatment of these pathologies by Cognitive-Behavioral Therapy (CBT). This article aims to investigate the treatment of ED by four therapists experts in this approach. The design used was the Multiple Case Studies. The information was collected through interviews. Consensus between the results were the importance of the therapeutic bond, interdisciplinarity, and family involvement in treatment. Among the advantages of CBT were cited: rapid and effective techniques. About the limitations were mentioned aspects such as low motivation of patients and economic issues. The main discharge criterion was a high properly functioning. Finally, all agree that further researches in the area are important. It should be noted especially the need for further research in the national context